A glutamic acid-based polymer keeping intact the integrity of all the three original functionalities of the amino acid. Issue 2 (17th February 2016) - Jamiu, Zakariyah A.; Al-Muallem, Hasan A.; Ali, Shaikh A.
Abstract: Dimethyl glutamate, on treatment with allyl bromide, afforded dimethyl N, N -diallylglutamate which upon alkaline ester hydrolysis followed by acidification with aqueous HCl gave N, N -diallylglutamic acid hydrochloride [(CH2 =CH–CH2 )2 NH + CH(CO2 H)(CH2 )2 CO2 H Cl − ]I . Using Butler's cyclopolymerization protocol, new monomerI underwent ammonium persulfate-initiated polymerization to give pyrrolidine ring-embedded linear cyclopolymerII i.e. −[−CH2 (C4 H6 )NH + {CH(CO2 H)(CH2 )2 CO2 H Cl − }CH2 −]− n retaining the integrity of all the three functionalities of glutamic acid. Under the influence of pH, the repeating units of triprotic acid (+) inII were equilibrated to those of water-insoluble diprotic polyzwitterionic acid (±)III, water-soluble monoprotic poly(zwitterion-anion) (±−)IV, and its conjugate base polydianion (=)V . The critical salt concentration required to promote water solubility of (±)III has been determined to be 0.548 M NaCl, 0.271 M NaBr, 0.133 M NaI. The basicity constants of the carboxyl groups and trivalent nitrogen in (=)V have been determined. A 5 ppm and 20 ppm concentrations ofIII are effective in inhibiting the precipitation of CaSO4 from its supersaturated solution with a ≈100% scale inhibition efficiency at 40 °C for a duration of over 3 and 16 h, respectively.